2001
DOI: 10.1897/1551-5028(2001)020<0652:praocp>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Risk Assessment of Cotton Pyrethroids: I. Distributional Analyses of Laboratory Aquatic Toxicity Data

Abstract: This is the first in a series of five papers that assess the risk of the cotton pyrethroids in aquatic ecosystems in a series of steps ranging from the analysis of effects data through modeling exposures in the landscape. Pyrethroid insecticides used on cotton have the potential to contaminate aquatic systems. The objectives of this study were to develop probabilistic estimates of toxicity distributions, to compare these among the pyrethroids, and to evaluate cypermethrin as a representative pyrethroid for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
73
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 29 publications
7
73
0
1
Order By: Relevance
“…However, its toxicity decreases significantly under natural in-field conditions as it undergoes microbial degradation, and also due to its good adsorptive properties (Schroer et al, 2004). Intensive application of deltamethrin causes toxicity to aquatic arthropods as well (Solomon et al, 2001). Deltamethrin is hydrophobic and has a high octanol-water coefficient which indicates a potential to bio-concentrate within aquatic organisms.…”
Section: The 'Definite Risk' Categorymentioning
confidence: 99%
See 1 more Smart Citation
“…However, its toxicity decreases significantly under natural in-field conditions as it undergoes microbial degradation, and also due to its good adsorptive properties (Schroer et al, 2004). Intensive application of deltamethrin causes toxicity to aquatic arthropods as well (Solomon et al, 2001). Deltamethrin is hydrophobic and has a high octanol-water coefficient which indicates a potential to bio-concentrate within aquatic organisms.…”
Section: The 'Definite Risk' Categorymentioning
confidence: 99%
“…Deltamethrin is hydrophobic and has a high octanol-water coefficient which indicates a potential to bio-concentrate within aquatic organisms. The bio-concentration of this pesticide can potentially cause toxicity to aquatic invertebrates and fish (Van der Werf, 1996;Solomon et al, 2001). …”
Section: The 'Definite Risk' Categorymentioning
confidence: 99%
“…This method characterized relative sediment toxicity for a compound using criteria from water-only studies by Solomon et al 19 No LC50 values could be found for chlordane and hexachlorocyclohexane (BHC), thus probable effect concentrations (PEC) were used, 20,21 and PEC values were normalized to 1% TOC. Meanwhile, it should be noted that R-and γ-chlordane values were summed together for TU analysis, and γ-BHC sediment PEC values were used to quantify β-BHC predicted TUs, as data for β-BHC were not available.…”
mentioning
confidence: 99%
“…In recently years, probabilistic approach which determines the probability of an exposure concentration exceeding the probability of effects has been increasingly used in ERA procedures (Solomon et al 2001;Carriger and Rand 2008). This is because, when used correctly, it can introduce greater statistical confidence into risk assessment when compared to traditional hazard quotient and assessment factor approaches (Wheeler et al 2002).…”
Section: Introductionmentioning
confidence: 99%